A marker free patient to digital image registration process - Gonçalves, Rafael L.; Magarotto, Felipe (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2013: Anais do XIII Workshop de Informática Médica, 2013)
Image guided surgery (IGS) is a routine practice in neurosurgery. The “real world coordinates” to digital image registration is the key for a precise navigation. In this work we developed a marker free patient real world to virtual digital image registration. By filtering just the surface points of the patient image we achieved a faster and more automatic registration process.